If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -8) = 12(3x + 24) Reorder the terms: 4(-8 + 2x) = 12(3x + 24) (-8 * 4 + 2x * 4) = 12(3x + 24) (-32 + 8x) = 12(3x + 24) Reorder the terms: -32 + 8x = 12(24 + 3x) -32 + 8x = (24 * 12 + 3x * 12) -32 + 8x = (288 + 36x) Solving -32 + 8x = 288 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. -32 + 8x + -36x = 288 + 36x + -36x Combine like terms: 8x + -36x = -28x -32 + -28x = 288 + 36x + -36x Combine like terms: 36x + -36x = 0 -32 + -28x = 288 + 0 -32 + -28x = 288 Add '32' to each side of the equation. -32 + 32 + -28x = 288 + 32 Combine like terms: -32 + 32 = 0 0 + -28x = 288 + 32 -28x = 288 + 32 Combine like terms: 288 + 32 = 320 -28x = 320 Divide each side by '-28'. x = -11.42857143 Simplifying x = -11.42857143
| -8k(k-4)-(-5k-5)=-4k | | 3x-2x+x= | | -16*-4= | | 2q-4=26forq | | 10x^2-3b-4=0 | | (2u-5)(9-u)=0 | | (2x-6)-(4x+4)= | | 40-3x=28 | | (x+2)(x+4)+2(x+2)(x-3)=0 | | 5=3(x-4)+2-2x | | 4y=9x-56 | | 12x^2-2x-1=0 | | 18-6b=10b+12 | | 4(2x+7)=6(3x-7) | | 14x+98=0 | | 100-5x=0 | | f(x)=x^2-3 | | V-8.3=6.54 | | 60+16s=60+16s | | h+8.5=-8.5 | | y=(x+10)-16 | | 23=a-22 | | x-8-4=1 | | 100-5x=25 | | 4n(n-9)=-81 | | -2(2y-1)=15 | | .09x+.08(13000-x)=1160 | | 400+13= | | 7x^2+84= | | (8)+3(1)=14 | | 3.5-1=3.5+-1 | | 5(3)-19=6y |